Performance Evaluation of a Communication Plan Implementation for Behaviour Change in People at Risk of Type 2 Diabetes in the Commune of Tchaourou in Benin of - METONNOU, Ericie Hermeline; AZANDJEME, COLETTE SYLVIE; SOSSA, JÉRÔME CHARLES; Paraiso, Moussiliou Noel; Bio Nigan, Issiako; AGUEH, VICTOIRE DAMIENNE AGOSSI (My University, 2022)
Introduction: There are very few programmes to delay or prevent diabetes in Africa. This study aims to evaluate the communication plan implementation to reduce risk factors for Type 2 diabetes in people at risk. Methods: The cross-sectional evaluative study focuses on the resources used for the implementation of the programme, the activities carried out and the beneficiaries of the programme. The non-probabilistic method was used to select. All target populations under study with appropriate sampling techniques. The performance of the communication plan implementation for behaviour change was assessed through the three sub-variables of evaluation of Donabedian health programmes: structure, process and results. The components assessment was based on the Varkevisser scale. The performance of the communication plan implementation for behaviour change was obtained by the sum of the scores of the three sub-variables. Results: The performance of the communication plan implementation for behaviour change was satisfactory in all programme villages at 89%. The establishment of the research team, the management team and the technical team, the availability of financial resources on a timely basis, the follow-up of nutritionists, sports teachers and peer educators, the implementation of the programme package and the home coaching of the targets were effective in all the programme villages of the study. The scores for structure performance, process performance, and results performance were 100%, 95%, and 83.8%, respectively. The involvement of the entire research team, the commitment of local authorities and the motivation of the targets were also important in the obtained result. Conclusion: This study shows that effective T2D preventive communication is possible at community level in Benin and probably in Sub-Saharan Africa.
Keywords: Implementation; People at Risk; Type 2 Diabetes; Benin